Validation of the Children’s International Cognitive Ability Resource (Ch-ICAR) - Dutry, Merel; Vereeck, Alexandra; Duyck, Wouter; Derous, Eva; Schelfhout, Stijn; Szmalec, Arnaud; Woumans, Evy; Schittekatte, Mark; Debeer, Dries; Dirix, Nicolas (Behavior research methods, 2025)
The International Cognitive Ability Resource, abbreviated ICAR, counters some of the practical problems researchers face when using good, but proprietary, licensed intelligence tests like the Wechsler tests, which include unfeasible administration times and financial costs. So far, ICAR has been validated for adolescents and adults in many countries, offering a viable test alternative for these populations. For use among children, however, the appropriateness of this resource was yet unknown. Therefore, we set out to develop a children’s ICAR: an instrument composed of ICAR-items, which provides a measure of cognitive ability in children between 11 and 14 years of age. The present article discusses the compilation process of the Ch-ICAR drawing from a pilot study, and evaluates its validity based on two additional studies. The pilot study involved 99 primary school pupils and aimed to select items for the Ch-ICAR instrument. Study 1 investigated the basic psychometric qualities of the Ch-ICAR in a sample of 820 secondary school pupils. Study 2 examined the construct validity by cross-validating the Ch-ICAR with on the one hand Raven’s 2 Progressive Matrices, and on the other hand the Flemish CoVaT-CHC Basic Version, relying on samples of 91 secondary and 96 primary school pupils, respectively. Results support the utility of the Ch-ICAR as a measure of children’s cognitive abilities within a research context.